O significado do momento da saída de adolescentes de instituição de acolhimento ao completarem a maioridade civil: e agora? - Honorato, Andreia Agda Silva (2011)
This present work, The meaning of the moment of the teenagers left the shelter institution when they are in age of majority: and now? , Andreia Agda Silva Honorato authorship, it presents a study from teenagers stories that leave their daily in a shelter at Santo André city, that is called, the School home São Francisco de Assis, composed by eleven home, where these teenagers are certain to leave the institution when they are 18 years old by the reason of the age of majority. Up to June, 2003, this shelter belonged to the Social Worker Department and, due the contradictory and bureaucratic factories, it was assumed by the Education Department (unique case in Brazil). They are young people that experience insecurities moments while results of contrary actions for an emancipator pedagogy. Based on the overall goal of knowing and identifying which the objectives and subjectives factories that contribute to the leaving more autonomous in the non shelter institutional act by the age of majority reason, seeking to break or soften with the aspects that permeate this moment and prevent that this process has been lived in safer way security understood here for beyond the economic factories. This way, the specifics objectives from this search were: To know the meanings attributed by the own subjects of the search teenagers that live the prior of non shelter like, it appropriates of the methodology applied daily in different historical moments of the shelter to comprehend, how much these refer to the lived results by these teenagers in the left moment. Between these specifics objectives and, from the two first, the existence premise is that to socialize the results of this search, could the shelter, rethink its methodology, to invest truly in article 92, subsection VIII that advocated the gradual preparation for the non shelter institutional, even as, that will be this study, considering as motivation to the operators of the public policy. It still firms, the intention to propose methodologies that come to contribute with the teenagers that will leave the shelter, considering the results from the studied bibliographies, but, mainly, the look of those people that live in this condition. This theme explain by the big demand of the teenagers that live, lived and will still live this condition, as well as, by production scarcity about the shelter left by age of majority reason, once that the studies search discuss the shelter process or the shelter daily. For both, it was realized two surveys. The first is about the historical institutional, by interviews with publics employees that act in different moments as manager or technical of the shelter; and, the second were collected testimony of the teenagers that left and are almost leaving the shelter institution by the age of majority reason. This is a study search qualitative no liable to generalization and presents like reflection document from meanings assigned by own subjects